Spatial and temporal pattern evolution and driving characteristics of rural settlements in Xilingol League from 1915 to 1980 - Sen Mu; Jianghong Zhen; Chun Xi (PLoS ONE, 2026)
Population migration and agricultural expansion have profoundly reshaped the rural characteristics of Xilingol League, a typical pastoral region in northern China. From the perspective of historical geography, this study investigates the settlement evolution in Xilingol League during 1915–1980. Drawing on declassified statistical data and historical documents, and employing kernel density estimation, hotspot analysis, and the geographical detector, we reconstruct and interpret the settlement patterns during the period without remote sensing imagery. The results reveal that: (1) Between 1915 and 1980, settlement expansion in Xilingol League exhibited a fan-shaped trajectory centered on Taibus Banner and Duolun County, with clustering intensity diminishing with increasing distance. (2) The 42°N parallel demarcates pastoral areas from agro-pastoral transitional zones, with settlements concentrated mainly in the transitional zone and showing a fragmented northeastward expansion into pastoral areas over time. (3) Socio-economic conditions were the dominant drivers of settlement evolution during this period, with cultivated land area ( q = 0.6266) and livestock numbers ( q = 0.6215) exerting the strongest explanatory power. This study provides new insights into the processes and driving mechanisms of modern settlement evolution in Xilingol League.